Pengaruh Dukungan Sosial dan Adopsi Teknologi Terhadap Kesejahteraan Buruh Tani di Desa Songan B Kecamatan Kintamani - Wati, Ni Putu Riski Krisna; Irwansyah, M. Rudi (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
The aim of this research is to examine the influence of social support and technology adoption on the welfare of farm workers in Songan B Village, Kintamani District. The location of this research was carried out in Songan B Village, Kintamani District, involving 160 farm workers as respondents. The sampling technique used is an incidental random sampling technique. The method used in carrying out the data collection process is in the form of a questionnaire using multiple linear regression analysis. The hypothesis testing process uses t and F tests using SPSS 25 for Windows. The results of this research, namely social support and technology adoption, show positive and significant results on welfare in the agricultural labor sector in Songan B Village, Kintamani District.